Exploring Research Idea Growth with Litmap: Visualizing Literature Review Graphically - Dwi Sulisworo (The Indonesian Institute of Science and Technology Research, 2023)
This study presents a method for tracking the growth of research studies in a particular field or topic using a graphical representation of literature review with the help of Libmap. The step-by-step method involves selecting an article or a set of articles that represent the topic of interest and using Libmap to analyze and visualize the relationships between different concepts and ideas. The study starts with the article entitled